Analysis of buckling of columns - Koh, Kin Hock. (2011)
Nowadays, composites in are widely used in industries due to its excellent mechanical properties comparing favorably on a cost/performance basis with traditional materials and also their high strength-to-weight ratio, stiffness comparing with most metals. However, buckling will still occur if the strength and stiffness criteria are violated, therefore the major design consideration for composite structure under cyclic compression stress is still column buckling. Euler-Bernoulli beam and classical lamination theory are used to create an analytical model in Excel format to obtain the critical buckling load of a laminated composite column. In addition, the experimental result from other FYP students are being compared with the analytical model showed good correlation. The comparison result shows that the coupling response is important variable and must be included in the computation of the effective flexural stiffness in laminated column. The aim of this project is to analysis the buckling effect of different ply angle, length and end condition used to reduce the failure of composite structural.